2015
DOI: 10.1097/aog.0000000000000977
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Preparation Before Dilation and Evacuation Using Adjunctive Misoprostol or Mifepristone Compared With Overnight Osmotic Dilators Alone

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 20 publications
4
36
1
Order By: Relevance
“…We demonstrate that using both misoprostol and mifepristone as an adjunct to synthetic osmotic dilators, fewer osmotic dilators achieved a similar cervical dilation compared with dilation reported in previous studies in this gestational age group . Thus, this use of medication adjuncts has the potential to decrease the pain and cost associated with osmotic dilator insertion and is consistent with previous work that focused on reducing from two sets of dilators to one .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We demonstrate that using both misoprostol and mifepristone as an adjunct to synthetic osmotic dilators, fewer osmotic dilators achieved a similar cervical dilation compared with dilation reported in previous studies in this gestational age group . Thus, this use of medication adjuncts has the potential to decrease the pain and cost associated with osmotic dilator insertion and is consistent with previous work that focused on reducing from two sets of dilators to one .…”
Section: Discussionsupporting
confidence: 88%
“…When osmotic dilators and misoprostol are used for cervical preparation, the addition of mifepristone does not seem to shorten procedure times (mean and median difference in procedure time was 1 minute). Previous larger studies showed more benefit with mifepristone as an adjunct to osmotic dilators in gestations >19 weeks and in nulliparous patients . The cost of mifepristone in some settings may be a barrier to its use and additional studies are needed to support routine use of mifepristone as an adjunct to osmotic dilators.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Same day procedures are possible with the use of osmotic dilators, especially with the use of Dilapan-S, which dilate quicker (4-6 hours versus 12-24 hour with laminaria) and increase more per volume (4 versus 3 times dehydrated dilator). 12,13 Thus, it is unclear if the use of osmotic dilators decreases the risk of major complications, but several studies have shown improved cervical dilation and provider satisfaction as compared to misoprostol alone.…”
Section: Management Of Vaginal Wall Perforationmentioning
confidence: 99%